Extra-Articular Manifestations of Rheumatoid Arthritis, Now - Paloma Vela (European Medical Journal Rheumatology, 2014)
Rheumatoid arthritis (RA) is a chronic systemic inflammatory disease, characterised by polyarthritis and extra-articular organ disease, including rheumatoid nodules, ophthalmologic manifestations, cardiopulmonary disease, vasculitis, neuropathy, glomerulonephritis, Felty’s syndrome, and amyloidosis. Extra-articular manifestations of RA (ExRA) occur in 17.8–40.9% of RA patients, 1.5–21.5% of them presenting as severe forms and usually associated with increased morbidity and mortality. They can develop at any time during the course of the disease, even in the early stages, and are associated with certain predisposing factors, such as the presence of rheumatoid factor, smoking, and long-standing severe disease. Rheumatoid nodules, the most common ExRA, have been found to be associated with the development of severe features, such as vasculitis, rheumatoid lung disease, pericarditis, and pleuritis, especially in those patients who develop them within 2 years from RA diagnosis. There is no uniformity in the definition of the term ExRA, which limits comparability between different studies. Several recent surveys suggest a lower frequency, probably due to a better control of disease activity. Diagnosis of ExRA is a challenge for clinicians, given its variable and complex presentation, and the lack of specific diagnostic tests; it must be based on clinical recognition and exclusion of other causes of the signs and symptoms. Furthermore, management continues to be difficult with a bad prognosis in many conditions. This article reviews the clinical aspects of major ExRA, focusing on incidence, clinical features, and therapeutic approaches, and how modern immunosuppressive therapy can change the outcome.